(untitled) (Interdisciplinary Studies Journal, 2026)
This article discusses meaningful learning in the teaching and learning process, highlighting its relevance as a transformative agent of pedagogical practices in the classroom. The proposal is justified by the need to rethink traditional teaching methods in the face of social transformations, technological and cognitive that directly impact the school contexto directly. Based on David Ausubel´s theory, the meaningful learning prior knowledge and promotes the construction of consistente relationships between new content and knowledge already acquired. In this sense, the study seeks to understand how such a conception can be applied to teaching practice, in order to favor educational quality through more engaging experiences, reflective and transformative. The adopted methodology includes a critical analysis that articulates theoretical and practical aspects of the implementation of this approach. To support the reference, They resort to authors as Ausubel, Kenski and Aragão, that reinforce the centrality of prior knowledge in the consolidation of lasting learning. The results show that meaningful learning is a fundamental milestone in the construction of knowledge, by enabling connections that remain in the student´s memory and contribute to more effective pedagogical practices. Thus, its integration with the teaching daily life representes a promising path to the continuous improvement of education.